STUDI KOMPARASI HASIL BELAJAR PENGGUNAAN MEDIA POWERPOINT MATA PELAJARAN EKONOMI KELAS X IIS - Annisa, Annisa; S, Bambang Genjik; Khosmas, F Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out a comparative of learning outcomes before and after using inpowerpoint learning media on economic subjects of class X IIS SMA Negeri 9 Pontianak. This research uses an experimental method, type of Quasi Experimental Design. In this study researchers were used 72 students as sample.The sampling technique used was purposive sampling. This study uses data collection tools in the form of direct observation techniques, tests, and documentary studies, to analyze the data in this study using descriptive analysis. After the prerequisite analysis test is carried out then hypothesis testing is carried out because the normal distributed data is followed by the T-test (t-test). Based on the results of the T-test calculation, the sig value is obtained. (2-tailed) at the pre-test and post-test Â is 0,03 where 0,03 is values less than 0.05 which meansaccepted as well as shows that powerpoint media contributes highly to economic learningÂ Keywords: Comparative study, learning outcomes, powerpoint learning media